Resolution Of Sharia Banking Disputes Through The Religious Courts And The National Sharia Arbitration Board (BASYARNAS) - Suryawansyah, Suryawansyah; Babussalam, A Basuki (Universitas Muhammadiyah Sumatera Utara, 2024)
Indonesian banking adheres to a dual banking system, conventional and sharia. Law (UU) No. 21/2008 on Islamic Banking is the legal basis for Islamic Banking in carrying out their operations, and in the event of a dispute, it can refer to article 55 (1) disputes can be resolved through the Religious Court (PA), and (2) resolved not by PA but can be with other forums and paragraph 2 is in line with Law No. 30/1999 on Arbitration and Alternative Dispute Resolution. Law No. 30 has led to to inconsistencies in resolving disputes, for example the practice of resolving financing contracts between banks and debtors who agree to resolve dispute at The National Shariah Arbitration Board (Basyarnas), but the implementation of dispute resolution is carried out at the PA. The results showed that the absolute authority to resolve sharia economic cases or the scope of Sharia Banking is the PA, but if the parties agree to settle at Basyarnas then the PA has not authorized in sharia economic cases